PTU-139 Usefulness of sechat scans in a dgh gastroenterology clinic. (17th June 2017) - Bhuva, M; Fayeye, F; Brookes, A; Boston, N; Harvey, J
Abstract : Introduction: SeHCAT (tauroselcholic [75 selenium] acid) can be used to investigate diarrhoea due to bile acid malabsorption (BAM). It is predominantly used in patients with diarrhoea-predominant irritable bowel syndrome (IBS-D) and Crohn's disease (CD). Historically these patients have been treated with bile acid sequestrants without a diagnosis however treatment is known to be poorly tolerated. NICE concluded in 2012 that SeHCAT is potentially useful, but that there is not enough evidence to demonstrate value for money. Method: A database of 53 patients who had undergone a SeHCAT scan at Bedford Hospital between June 2014 and June 2016 were retrospectively reviewed. BAM was defined as less than 15% retention of SeHCAT after one week. Data was subsequently analysed to look at severity and type of BAM, and treatment methods were reviewed. Results: Of the 53 patients, 28 were diagnosed with BAM following scanning with SeHCAT. The average age was 45 years old, with 75% being female. 10 of the 28 patients had type 1 BAM (9 with CD without ileal resection, and 1 with an ileal resection for ischaemic bowel). 10 of the 28 patients had type 2 BAM (idiopathic) whilst the remaining 8 had other GI pathology and were diagnosed with type 3 BAM. 13 of the 28 patients had 0%–5% retention indicating severe BAM, and 8 of the 13 had a diagnosis of Type 1 BAM. 3 patients who were started on colestyramine did not find it useful, and 6 could not tolerate the medication. 6 patients were subsequently trialled on colesevelam with no positive response. Dietetic manipulation was found to be the most successful treatment, with 6 patients responding to a diet low in FODMAP. However, these patients all had IBS-D rather than CD. Conclusion: Interestingly, 10 out of 13 CD patients (77%) were diagnosed with BAM, and 8 of them were diagnosed with severe BAM (SeHCAT retention <5%). All of these Crohn's patients were on treatment for their CD. Therefore, if patients with CD who are in remission remain symptomatic on treatment and calprotectin is low indicating a low level of inflammation, there should be a high index of suspicion for BAM and SeHCAT scanning would be advisable. Colestyramine costs £730 a year on average (based on a dose of 2–3 sachets per day at a cost of £31.84 for 50 sachets). Colesevelam is more expensive, and costs £1170 a year on average (based on a cost of £96.10 for 180 capsules). SeHCAT scanning costs £436–486 according to NICE. Adherence and reported response to treatment are poor. This study highlights that formal diagnosis is more financially desirable than blind treatment. As medications are poorly tolerated and long term dietary manipulation may be the best treatment for BAM Type 2, especially for IBS-D patients, a diagnosis is crucial. Reference: . NICE guidleines 2012- https://www.nice.org.uk/guidance/dg7 Disclosure of Interest: None Declared